Rectangular p-periodicity and pq-periodicity of a rational difference system - D.S. Dilip; Sibi C. Babu (Examples and Counterexamples, 2021)
In this paper, we classify periodic characters of the positive solutions of the difference system (1) xn+1=αe−(yn+xn−1)β+yn+xn−1,yn+1=γe−(xn+yn−1)δ+xn+yn−1as rectangular p-periodic and pq-periodic solutions, where the constants α,β,γ,δ,x−1,x0,y−1,y0>0. Moreover, we do bifurcation analysis and observe various forms of periodic characters of solutions of (1). Also an open problem regarding the newly classified periodic character is proposed.